Proposed New Business Model on Virtual Reality Tour Based on Customer Segmentation (Case Study of PT Telkom Indonesia) (The Indonesian Journal of Business Administration, 2021)
A virtual reality tour or VR tour is one of the current tourist industry trends. Virtual tours have become widely known since the pandemic, and virtual tours are an alternative to entertainment while at home. Nevertheless, the use of VR in Indonesia itself is still relatively minimal. Seeing the opportunities in the development of VR in Indonesia, PT Telkom has the initiative to develop VR tours with the theme of ten new Balis as a collaboration with the ministry of tourism to promote tourist destinations. However, due to the lack of use of VR in Indonesia, PT Telkom is still unable to determine the right target market for the development of this virtual tour business. The target market is the first step to determine the business model that Telkom wants to develop. In developing a virtual tour that is in accordance with the wishes of consumers, this research conducted a survey of customers. The survey was conducted using an open-ended survey to gain insight from customers on virtual tours. Based on the survey results, the root of the problem lies in the lack of experience they get when using virtual tours because the content such as images and videos received is unclear. From this problem, a solution is made in a business model to develop a virtual tour tailored to the customer's needs using lean business model. In implementing the implementation plan, the author recommends using pirate metrics starting from the awareness of potential customers to how potential customers can invite other potential customers to use this virtual tour.Keyword: Customer Segment, Lean Business Model, VR, Virtual Tour